2011
DOI: 10.1080/01140671.2011.560165
|View full text |Cite
|
Sign up to set email alerts
|

Sexual compatibility and floral biology of some olive cultivars

Abstract: Pollen tube observation was used to assess the self-and cross-incompatibility of the olive (Olea europaea L.) cultivars 'Frantoio', 'Koroneiki' and 'Kalamata'. The pistils were harvested 1 week after hand pollination and stained with 0.1% aniline blue. The styles and ovules were separated, mounted in 80% glycerol and observed under a fluorescence microscope. All the cultivars studied were self-incompatible. 'Frantoio' (as a host) was incompatible with 'Koroneiki' and 'Barnea' but partially compatible with 'Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
2
20
0
3
Order By: Relevance
“…More recently, Seifi et al. (), Seifi, Guerin, Kaiser, and Sedgley () and Vuletin Selak, Cuevas, Goreta Ban, and Perica () examined crosses between other varieties and concluded that observations of pollen tube progression are easy, but whether one or two pollen tubes reach one of the ovules is not so easy to determine in practice. Thus, the method remains delicate to routinely ascertain whether fertilization has occurred, and the observation of fertilization is a key step to establishing compatibility or incompatibility.…”
Section: Comparing Results Of (Saumitou‐laprade Vernet Vekemans Bimentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Seifi et al. (), Seifi, Guerin, Kaiser, and Sedgley () and Vuletin Selak, Cuevas, Goreta Ban, and Perica () examined crosses between other varieties and concluded that observations of pollen tube progression are easy, but whether one or two pollen tubes reach one of the ovules is not so easy to determine in practice. Thus, the method remains delicate to routinely ascertain whether fertilization has occurred, and the observation of fertilization is a key step to establishing compatibility or incompatibility.…”
Section: Comparing Results Of (Saumitou‐laprade Vernet Vekemans Bimentioning
confidence: 99%
“…(, ), Seifi et al. (), and Spinardi and Bassi (), paper bags were used. The different materials of which bags are made are important because of their possible permeability to pollen grains.…”
Section: Regarding Pollen Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different letter indicates significant difference within a row at P ≤ 0.05. Table 4 show thatinflorescence length and flower number varied from shoot to shoot, tree to tree, cultivar to cultivar and from year to year as early reports (Lavee et al, 1996, Lavee et al, 2002and Seifi et al, 2011. Panicle length of' Toffahi 'and 'Aggizi'cvs.…”
Section: Inflorescence Structure and Characteristicsmentioning
confidence: 91%
“…Thus, estimation of flower density and subsequent fruit set is important in assessment of a cultivar's performance (Socias i Company, Felipe, Aparisi, García, & Dicenta, 1998). Seifi, Guerin, Kaiser and Sedgley (2011) reported that in olive (Olea europaea L.) cultivars, the section of shoot (upper, middle, and basal) affected the inflorescence length and the number of flowers per inflorescence, but not the percent of perfect flowers present. They also found that shoot orientation (north, south, east, and west) did not have any influence on these characteristics in all studied cultivars.…”
Section: Introductionmentioning
confidence: 99%